(untitled) (Revista Española de Fisiología, 1985)
The effects of two dopaminergic blockers, pimozide and domperidone, on the prolactin secretion were investigated in adult female rats treated neonatally with estrogens (100 micrograms of estradiol benzoate s.c.on day 1).These rats showed hyperprolactinemia (556 micrograms/l vs 57.7 in oil-injected) and treatment with pimozide or domperidone failed to increase prolactin levels in the adult age.These results suggest that the hyperprolactinemia in neonatally estrogenized female rats is produced by loss of the dopaminergic inhibition on prolactin secretion, so that the pharmacological blockade of dopaminergic receptors is uneffective.The dopamine levels in hypothalamus were similar in control and estrogenized females suggesting that failure in dopaminergic inhibition is due to a decrease in dopamine secretion to portal vessels.